Shining a light on disability and health communication. (2nd October 2022) - A. Manganello, Jennifer
ABSTRACT: Examining health inequities in the context of communication related to health and health care is important for creating health equity. There has been an increasing number of studies conducting health communication research to address inequities, but research that has prioritized people with disabilities remains limited. Over the past year, there has been a growing focus on disability and health research, including peer-reviewed papers in this volume. The health communication field can build on this momentum to continue to focus on disability in topics related to health information, misinformation, health literacy, interpersonal communication, media campaigns, media representation, digital health, communication technologies, and more.